Effectiveness of social media marketing as a sustainable futuristic tool for consumer decision-making process - Haque, A K M Ahasanul; Agarwal, Khushbu (Apple Academic Press, Taylor and Francis Group, 2024)
The most recent development in Industry 4.0 and the marketing sector is social media marketing (SMM). Making impactful conversations is the cornerstone of success for any media (Agarwal, 2013). The latest sustainable marketing strategy is social media marketing, which is built on the widely accepted idea of word-of-mouth marketing (WOM). India is currently the seventh-largest internet market in the world, with a growth rate of 11.2. India now has 60.5 million active social media users, up from 38 million in November 2011 (Agnihotri, Kothandaraman, Kashyap, & Singh, 2012). In a nutshell, social media websites in India see annual growth rates of around 100. Despite the tremendous growth of social media in India over the past few years, there are still many untapped potentials (Amerian & Pisarava, 2012). This research aims to raise awareness among marketers of Industry 4.0 and Industry 5.0 worldwide about the power of social media in spreading sustainable environmental messages at large. The impact of sustainable social media marketing strategies on consumer behavior is the main focus of the current research work. A sample of 358 social media users was chosen to achieve the goal. According to the report, the majority of consumers are most aware of social media marketing and product photographs and videos. Findings indicated that making sustainable buying decisions on social media is greatly influenced by how easily one can find information. Customers were asked to indicate their satisfaction with different factors of social media, and they are highly satisfied with the ease of searching for information on social networks. Poor response systems, physical unavailability of products, improper replacement facilities, and lack of reliability of information were considered major barriers by customers in stimulating or satisfying their purchase decisions. © 2025 by Apple Academic Press, Inc.